2021
DOI: 10.1016/j.ultsonch.2021.105509
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanism of ultrasound against Escherichia coli: Alterations in membrane microstructures and properties

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 57 publications
7
52
0
Order By: Relevance
“…Further studies also report the presence of ghost cells following ultrasound on a range of biological samples including E. coli , L. innocua , S. aureus, blood cells, and yeast [6] , [46] , [90] , [95] , [96] , [97] . Many other studies also show evidence of cell breakage and debris following ultrasound treatment at a range of frequencies, further lending to the theory that inactivation by ultrasound involves the disruption of the cell membrane through various mechanisms such as pore formation, mechanical disruption by pressure shock waves, jetting and shear effects [6] , [46] , [55] , [98] , [99] , [100] , [101] .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Further studies also report the presence of ghost cells following ultrasound on a range of biological samples including E. coli , L. innocua , S. aureus, blood cells, and yeast [6] , [46] , [90] , [95] , [96] , [97] . Many other studies also show evidence of cell breakage and debris following ultrasound treatment at a range of frequencies, further lending to the theory that inactivation by ultrasound involves the disruption of the cell membrane through various mechanisms such as pore formation, mechanical disruption by pressure shock waves, jetting and shear effects [6] , [46] , [55] , [98] , [99] , [100] , [101] .…”
Section: Resultsmentioning
confidence: 77%
“…Inactivation of E. coli and S. aureus was also observed at 30 kHz and 100 W with a horn configuration [90] . Other studies conducted at low frequencies (20–44 kHz) and high powers also report microbial inactivation for E. coli [51] , [55] , [63] , [91] .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…At present, the application of US to protein and sterilization has received extensive attention. US can cause cavitation bubbles, high temperature, high pressure, etc., which may destroy the structure of microorganisms, change the structure and functional properties of proteins, thereby improving the quality of aquatic products [4] , [5] . In addition, US treatment is a “green” technology that reduces energy usage, shorter processing time and no chemical additives, making consumers more at ease [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Pedrós-Garrido et al [3] also found that the US with high intensity (30 kHz, 51.41 W/L) treatment for 45 min could significantly reduce microbiological counts and improve the quality of salmon ( S. salar ), mackerel ( S. scombrus ), cod ( G. morhua ) and hake ( M. merluccius ) fillets. He et al [4] reported that the number of Escherichia coli O157:H7 was decreased 0.76–3.52 log CFU/mL with US treatment (64, 191, 372, and 573 W/cm 2 , 20 kHz) for 27 min. However, Huang et al [8] found that dual-frequency ultrasound had a wider scope of energy dissipation compared with single-frequency ultrasound.…”
Section: Introductionmentioning
confidence: 99%